The Effect of Composted Oil Palm Empty Bunches on Growth and Yield of Pakchoi Plants in Ultisol Soil - Wahdah, Rabiatul (TROPICAL WETLAND JOURNAL, 2023)
Ultisol faces several challenges as agricultural land, including high soil acidity, low organic matter content, macro-nutrient deficiencies, and low cation exchange capacity that need to be addressed. One proposed solution is the use of oil palm empty fruit bunch (EFB/TKKS) compost, which is rich in N, K, and organic C. This compost can improve the physical properties and soil structure, making it a potential alternative for amending Ultisol. Pakchoi, a vegetable rich in vitamins and minerals, has broader stems and leaves compared to regular green mustard. It thrives in various conditions, both lowland and highland, and has a substantial market demand. This research aims to assess the impact of EFB/TKKS compost application on the growth and yield of pakchoi in Ultisol and to determine the optimal dosage. The study employs a Completely Randomized Design (CRD) with one factor, consisting of 5 treatments and 4 replications, totaling 20 experimental units. The treatments include t0 = TKKS compost 0 ton ha-1, t1 = TKKS compost 15 ton ha-1, t2 = TKKS compost 20 ton ha-1, t3 = TKKS compost 25 ton ha-1, and t4 = TKKS compost 30 ton ha-1. The results indicate that the application of TKKS compost significantly influences the growth and yield of pakchoi in Ultisol, with the optimal dosage identified at 20 ton ha-1.